The Influence of Financial Literacy and Financial Technology on the Consumptive Behavior of University Students in Sintang Regency - Joko Susilo; Yasir Hudzaifah; Ega Lestari (Yayasan Pendidikan Islam Bustanul Ulum Mojokerto, 2026)
This study investigates the influence of financial literacy and financial technology on the consumptive behavior students in Sintang. Adopting a structured quantitative research design, the study analyzes these economic phenomena through empirical hypothesis testing. To ensure data representativeness, a purposive sampling technique was applied to select 300 student respondents who met the predefined criteria, though it is acknowledged that this non-random sampling approach may limit the generalizability of the findings beyond the specific institutional and regional context examined. Data collection was conducted via questionnaire instruments that satisfied the rigorous standards for both validity and reliability. Ultimately, the analytical phase employed Partial Least Squares-Structural Equation Modeling (PLS-SEM) facilitated by the SmartPLS 4.0 software platform. The empirical findings indicate that financial literacy exerts a significant negative influence on the consumptive behavior of students (p-value = 0.000 < 0.05), thereby highlighting the critical role of financial competence in regulating and managing daily spending habits. In contrast, the structural analysis reveals that financial technology demonstrates a non-significant effect on student consumptive behavior, as supported by a p-value of 0.136, which clearly exceeds the established statistical significance threshold. While the sample size of 300 respondents is considered adequate for PLS-SEM analysis, caution should be exercised when generalizing these conclusions to students from different institutions, regions, or socioeconomic backgrounds.